Electrical submersible pumps manual : design, operations, and maintenance - Takács, Gábor, 1947- (Gulf equipment guides., 2009)
Ideal for removing large amounts of liquids from wells, Electrical Submersible Pumps (ESP) are perhaps the most versatile and profitable pieces of equipment in a petroleum company's arsenal. However, if not properly maintained and operated, they could quickly become an expensive nightmare. The first book devoted to the design, operation, maintenance, and care, Electrical Submersible Pumps Manual delivers the tools and applicable knowledge needed to optimize ESP performance while maximizing of run life and the optimization of production. The prefect companion for new engineers who need to develop and apply their skills more efficiently or experienced engineers who wish further develop their knowledge of best practice techniques, this manual covers basic electrical engineering, hydraulics and systems analysis before addressing pump components such as centrifugal pumps, motors, seals, separators, and cables.